A Pilot Study Examining Neural Response to Pain in Adolescents With and Without Chronic Pain - Jones, Scott A.; Cooke, Holly E.; Wilson, Anna C.; Nagel, Bonnie J.; Holley, Amy L. (Frontiers in Neurology, 2020)
Introduction: Chronic pain is common in adolescence and is associated with both pain and prevalence of mental illness later in life. While previous functional neuroimaging work has informed knowledge of neural alterations associated with chronic pain, these findings have been primarily limited to adult samples, and it is unclear if similar patterns of altered brain activation are present in the developing adolescent brain. Objectives: The purpose of this study was to pilot a noxious pressure task during functional neuroimaging to assess brain response to pain in adolescents with and without chronic pain. Methods: Adolescents (ages 11-16) with (n=9, 7 females) and without (n=9, 7 females) chronic pain, matched on age, sex, IQ, and parental history of chronic pain, completed a noxious mechanical pressure task to assess subjective pain thresholds. This was followed by randomized presentation of subjective equivalent pressure applications (adolescents’ pain 4/0-10), and two objectively equivalent pressures (0.25 kg/cm2 and 1.5 kg/cm2), during functional magnetic resonance imaging, using an event-related task design. Results: Findings revealed that adolescents with chronic pain demonstrated significantly greater activation in the posterior cingulate compared to controls. Further, all adolescents demonstrated significant pain-related brain response in brain regions implicated in pain neurocircuitry, as well as in several regions of the default mode network. Similar patterns of neural response were also noted during pain anticipation. Conclusion: These findings are important for not only understanding the neurocircuitry involved in adolescent chronic pain, but may prove beneficial to future pain treatment efforts that seek to alter pain neurocircuitry.